A Blended Learning Model of Peer Support Training Program for Women with Breast Cancer - Komatsu, Hiroko; Yagasaki, Kaori; Osaka, Wakako; Yamauchi, Hideko; Nakamura, Seigo (International Journal of Advanced Nursing Studies, 2012)
Objectives: Peer support is an important social support for cancer patients. A blended learning model of peer support training program in breast cancer was tested for feasibility. Methods: We developed a peer support training program for women with breast cancer with a blended learning approach combining face-to-face methods with e-learning. After face-to-face orientation, a 20-session e-learning program was provided on the Web followed by a one-day workshop including role playing. Log-files were recorded to assess the pattern of use in the e-learning program. The usability and acceptability were assessed by an evaluation questionnaire with a 5-point Likert scale. Psychosocial outcomes were assessed over time (baseline, post-program, and 3-month follow-up) using repeated measured one-way analysis of variance. Results: Twenty-eight women with breast cancer experience were recruited to the study. The rates of retention and assessment completion were high (92.9% and 89.3%, respectively). Participants favorably rated on the usability of the program. The mean time taken to complete the total of 20 sessions in the e-learning program was 18.69 days. There were no adverse psychosocial effects on the participants. Conclusions: The blended learning model of the breast cancer peer support training program was feasible and well accepted by the peer support volunteers.